A Program Applying Professional Safety Basics in Construction Projects (Journal of Engineering, 2016)
When industrial and  constructional renaissance started in the world, the great interest was going on towards the equipment’s,  which was the first mean for production. After industry was settled the interest was going on towards the men ship which manpower on which the production depends. It was approved that it represents the basic part in all of the processes and the protection of those individuals against dangers of these equipment’s, industry and its accidents was the basic things which was studied in many researches until it crystallized in general principles for all industries and other take care in each industry.     The professional safety is concerned as restrict which aims to take care of humanitarian and material principles also to raise the production of these principles, in the aspect of safety, health and providing the suitable healthy condition to the worker so he can feel safety, confidence and sociological settle, this will increase the production. So In order to maintain the manpower of business risks and to enable them to fulfill their role better to increase production and improve the quality and maintain the machine and supporting the national economy and keep pace with industrial developments and technological came the idea of research to focus on the importance of studying the subject of occupational safety by conducting a field survey to see the reality of professional safety in the relevant departments and work sites and through a questionnaire on the subject and conduct personal interviews with those concerned in this area and to prepare a program for the application of professional safety for each resource (labor, machines, materials, money) in construction sites and departments concerned.